2023
DOI: 10.5377/alerta.v6i1.15445
|View full text |Cite
|
Sign up to set email alerts
|

Estrés laboral y salud mental del personal de primera línea en la atención de la COVID-19

Abstract: Introducción. El estrés laboral significó un riesgo importante para la presencia de alteraciones de salud mental en trabajadores de salud, durante la pandemia de Coronavirus 2019. Objetivo. Determinar la relación del nivel de estrés laboral y salud mental en el personal asignado en primera línea de atención contra el COVID-19. Metodología. Se realizó un estudio transversal analítico en las áreas de emergencias y hospitalización del Hospital Nacional San Juan de Dios de San Miguel, de septiembre a diciembre de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…In Latin America, we can address these alterations. The study by Magaña-Salazar et al, (2020), carried out in El Salvador on workers at a second-level hospital (which included clinical and non-clinical staff), identified a prevalence of depression of 9.1%, 51.2% had minor anxiety and 13.2% had major anxiety [29]. When compared with the population of the present study, a higher prevalence of major anxiety was observed (33.5%), although it was slightly lower in the anxiety rating (42.1%) and twice the proportion of workers with depression (18.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Latin America, we can address these alterations. The study by Magaña-Salazar et al, (2020), carried out in El Salvador on workers at a second-level hospital (which included clinical and non-clinical staff), identified a prevalence of depression of 9.1%, 51.2% had minor anxiety and 13.2% had major anxiety [29]. When compared with the population of the present study, a higher prevalence of major anxiety was observed (33.5%), although it was slightly lower in the anxiety rating (42.1%) and twice the proportion of workers with depression (18.9%).…”
Section: Discussionmentioning
confidence: 99%
“…When compared with the population of the present study, a higher prevalence of major anxiety was observed (33.5%), although it was slightly lower in the anxiety rating (42.1%) and twice the proportion of workers with depression (18.9%). The personnel with the greatest impact on their mental health, according to Magaña-Salazar et al, (2020), were the nursing and non-clinical personnel, something that could not be identified in the Mexican nursing personnel but was the case for the non-clinical personnel [29].…”
Section: Discussionmentioning
confidence: 99%
“…Se encontró estrés laboral y alteraciones de salud mental, principalmente, entre las edades de 21 a 40 años. Los trabajadores de enfermería, radiología y de servicios generales presentaron niveles altos de alteración en la salud mental 1 .…”
unclassified
“…Por otro lado, es importante realizar un diagnóstico de la situación de salud de los trabajadores con el fin de evitar un desempeño inadecuado, mediante la ejecución de intervenciones oportunas, entre ellas, procesos de gestión orientados a la mejora de las áreas y horarios de descanso, los tiempos para la alimentación, las reuniones lúdicas para la atención de emociones, la rotación continua del personal, así como el abastecimiento de los insumos necesario para realizar las labores, incluidos los equipos de bioseguridad 1 .…”
unclassified
See 1 more Smart Citation